The Relationship Between Teenagers' Perception of Parental Discipline and Academic Procrastination in an EFL Context - Bakri, Fitriyani; Halim, Abdul; Hasbi, Muh. (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2024)
Abstract. This research aims to find out the relationship between teenagers' perception of of parental discipline and the academic procrastination in an EFL context of students at SMA 1 Bulukumba. This research is descriptive quantitative research and sampling was carried out using the random sampling method. Research data was collected using a Likert scale regarding teenagers' perceptions of the implementation of parental discipline and academic procrastination. Based on the results of data analysis using SPSS, the normality test yielded a significance value (Sig) of 0.009. This indicates that the data is derived from a population that follows a normal distribution. Then, the linearity test revealed a negative (-) direction of the relationship between adolescents' perceptions of parental discipline and academic procrastination. The linearity coefficient of 0.79 indicates that 79% of the variation in academic procrastination can be explained by perceptions of parental discipline. Thus, hypothesis test: the correlation coefficient of 0.138, obtained through the SPSS program, indicates the relationship between adolescents' perceptions of parental discipline and academic procrastination. Keywords: teenagers’ perception, parental discipline, academic procrastination